Pengaruh Peran Pendidik dalam Membentuk Karakter Peserta Didik pada Mata Pelajaran Pendidikan Pancasila Kelas III SD - Fitri Nanda Shafira; Dayu Rika Perdana; Amrina Izzatika; Muhammad Nurwahidin (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is based on the problem of declining morals of third-grade students at SD IT Baitul Muslim, which has implications for daily behavior, particularly in Pancasila Education learning. Students tend to exhibit attitudes that are inconsistent with positive character values, such as a lack of tolerance and a low sense of love for the homeland. The purpose of this study is to identify the significant influence of educators' roles in shaping the character of third-grade elementary school students in Pancasila Education subjects. The method used is an ex post facto method with a quantitative approach and a purposive sampling design. The study population consisted of 10 educators and 95 students, with a sample of 10 educators and 40 students from two selected classes. Data collection techniques were carried out through questionnaires and documentation that had been tested for validity using Aiken's V and reliability with Cronbach Alpha. Hypothesis testing using simple linear regression analysis showed a significance value of 0.044 which is smaller than 0.05 and a calculated F value of 5.692 which is greater than the F table of 2.27. Thus, the null hypothesis is rejected and the alternative hypothesis is accepted. The research findings confirm the significant influence of educators, particularly as demonstrators, classroom managers, facilitators, and evaluators, in shaping students' character in Pancasila Education. The implication of these findings is that educators need to optimize role models to improve students' character development.